173k views
2 votes
Help please! Note: Use ELIMINATION!!!

Help please! Note: Use ELIMINATION!!!-example-1
User Rod Rob
by
6.7k points

2 Answers

5 votes
Multiplying the second equation by 4/3 and adding it to the first, we get 36=9x and by dividing both sides by 9, we get x=4. Next, we can plug that into the second equation (it doesn't matter which equation) to get 3*4-3y=18=12-3y. Subtracting 12 from both sides, we get 6=-3y and by dividing both sides by -3 we get y=-2
User Jake Alsemgeest
by
7.3k points
2 votes
the answers are 24 and -2

User Aymen TAGHLISSIA
by
7.7k points